Pengaruh Status Putus Sekolah dan Sosio-Ekologis Terhadap Ketahanan Remaja Perempuan dari Pernikahan Dini di Pulau Sulawesi - Putri, Afriani Kartika; Dokhi, Mohammad (Politeknik Statistika STIS, 2024)
For the realization of the Golden Indonesia 2045, adolescents as the next generation of the nation are expected to become quality human resources. However, various problems in adolescents can hinder the achievement of the nation's progress, especially dropping out of school and early marriage. Therefore, this study aims to determine the characteristics of adolescent girls and the variables that affect their survival from early marriage by considering unobservable factors grouped by province in Sulawesi Island. The method used is survival analysis with the Weibull AFT Gamma Shared Frailty model based on the March 2023 Susenas data. This study show that the age of the spouse, migrant status, region of residence, school dropout status of adolescent girls, and school dropout status of the spouse affect the early marriage of adolescent girls, with the age of the spouse as the most influential factor. Dropping out of school was also shown to accelerate the timing of early marriage of adolescent girls by 0.941 times when the adolescent girl dropped out of school and by 0.963 times when she had a partner who dropped out of school. There was also a shared frailty effect in Sulawesi Island.